PENDIDIKAN GENDER SEJAK USIA DINI MELALUI HYPNOPARENTING - Betty Yulia Wulansari (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2017)
Sexual violence that occurs in children is increasing. Girls are more prone for being victimized by malicious perpetrators. Children are abused, tainted and killed as if their lives are worthless. Child protection law from sexual crimes has been applied in Indonesia. However, it still needs some self-prevention from the children. Gender education is one of the efforts in protecting girls from sexual violence. Early gender education is intended so that girls will be able to take care of themselves from their gender opponents. Gender education can be delivered by parents to their daughter through hypnoparenting method before bedtime. This method combines the aspects of early childhood characteristics with theta wave in the brain. Hypnoparenting suggestions will stay in children’s long-term memory so it is appropriate to instill gender education since in the early age. Keyword: gender education, hypnoparenting, early age children.